Across the spectrum of women and crime: theories, offending, and the criminal justice system - Sharp, Susan F. (Carolina Academic Press, 2016)
Introduction / Susan F. Sharp -- Theorizing about crime and women -- Exploring the relationship between gender and strain : two case studies / Alana Van Gundy-Yoder -- Female offenders as victims of IPV : exploring Maslovian cracks in the system / Alisa Smith and G. Jeffrey Klepfer -- Wanda Jean Allen : a case of multiple marginality / Susan F. Sharp -- Arresting girls for dating violence : the importance of considering intersectionality / Alesha Durfee -- Varieties of female offenses -- Gender, romance and filicide / Wendy R. Dragon, Michelle Oberman & Cheryl L. Meyer -- Dancing, stripping, and escorting : women's experiences of money, drugs, and prostitution in the legal sex work industry / Gail A. Caputo -- "I'll hook you up" : women's experiences selling & trading methamphetamine / Robert Jenkot -- Terrorism and the female suicide bomber / Vesna Markovic -- The system responds -- Women and wrongful conviction : how? whom? why? / Michael H. Fox -- Women's experiences with imprisonment : from silence to resistance / Jodie Lawston -- Inequality among female offenders : racial disparities in substance abuse and medical treatment among mothers in prison / Zina T. McGee, Kaneesha Williams, Nicollette Strickland, Tamara Dobson-Brown, Mykeya Foreman -- Second-chance grandparenting : how a new and renewed identity impacts the desistance process / Erin M. Kerrison and Ronet Bachman -- Staying out or going back? : a qualitative study of women prisoners, recidivism and reintegration / Susan F. Sharp and Juanita Ortiz -- Conclusions: so, what does it all mean? / Susan Marcus-Mendoza and Susan F. Sharp